2016
DOI: 10.1093/gbe/evw246
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Regions Symptomatic of Conformational and Functional Flexibility to Identify Antiviral Targets in Current and Future Coronaviruses

Abstract: Within the last 15 years, two related coronaviruses (Severe Acute Respiratory Syndrome [SARS]-CoV and Middle East Respiratory Syndrome [MERS]-CoV) expanded their host range to include humans, with increased virulence in their new host. Coronaviruses were recently found to have little intrinsic disorder compared with many other virus families. Because intrinsically disordered regions have been proposed to be important for rewiring interactions between virus and host, we investigated the conservation of intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…These targets represent potential drug-binding sites located in protein regions crucial for viral fitness and, therefore, conserved on long evolutionary time scales. Our study identified two to four such targets in the protease (NSP5), replicase (NSP7), helicase (NSP13) and exonuclease (NSP14), with nine targets identified in the RdRP (NSP12) [7].…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…These targets represent potential drug-binding sites located in protein regions crucial for viral fitness and, therefore, conserved on long evolutionary time scales. Our study identified two to four such targets in the protease (NSP5), replicase (NSP7), helicase (NSP13) and exonuclease (NSP14), with nine targets identified in the RdRP (NSP12) [7].…”
Section: Introductionmentioning
confidence: 90%
“…A multiple sequence alignment of RdRP from SARS-CoV-2 (accession number: YP_009724389.1, range 4398-5324) and the RdRP sequences previously used to determine the target motifs [7] was constructed using mafft with L+INS+ i in Jalview [12]. The multiple sequence alignment was used to build a phylogenetic tree using PhyML with 100 bootstraps [13].…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 3 more Smart Citations